2016
DOI: 10.1021/acs.jcim.5b00596
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel Nonactive Site Inhibitors of the Prothrombinase Enzyme Complex

Abstract: The risk of serious bleeding is a major liability of anticoagulant drugs that are active-site competitive inhibitors targeting the Factor Xa (FXa) prothrombin (PT) binding site. The present work identifies several new classes of small molecule anticoagulants that can act as nonactive site inhibitors of the prothrombinase (PTase) complex composed of FXa and Factor Va (FVa). These new classes of anticoagulants were identified, using a novel agnostic computational approach to identify previously unrecognized bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…These compounds had no previously known biological functions. Thus, we have shown that our virtual high-throughput screening approach can successfully identify novel chemical probes for specific targets, complementing other recent successes using the same approach (78).…”
Section: Discussionmentioning
confidence: 55%
“…These compounds had no previously known biological functions. Thus, we have shown that our virtual high-throughput screening approach can successfully identify novel chemical probes for specific targets, complementing other recent successes using the same approach (78).…”
Section: Discussionmentioning
confidence: 55%
“…The computational hits were analyzed using two criteria- i) binding energies as predicted by Vina and ii) “snapshot count” [ 43 ], giving the number of MD snapshots to which one specific compound is predicted to bind. This allowed the identification of compounds predicted to bind with high binding affinities to multiple conformations of the TM and VFT domains of GPRC6A.…”
Section: Methodsmentioning
confidence: 99%
“…As stated above, these structures generally represent a static snapshot of a major functional state of the target protein. More recently, the single-point docking approach has been improved to take into account thermal and conformational fluctuations of such major conformational states of the protein in an approach referred to as ensemble docking; the approach has been shown to further enhance both the quality and the efficiency of lead predictions 10 and successfully applied to a number of protein targets 11,12 (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%